The Influence of Herbarium-STEM on Students’ Interest of Becoming the Plant Taxonomists - Samsuar, Samsuar; Zaki, Ammar; Rahmi, Rahmi; Salsabila, Rachmah Putri (Universitas Islam Negeri Ar-Raniry, 2025)
Taxonomy study in Indonesia is still a concern due to non-innovative learning methods that cause students not interested in learning and conducting research on it. Consequently, it was impacted by the lack of Indonesian Plant Taxonomists. This research aimed to determine the influence of Herbarium-STEM on students' interest in becoming The Plant Taxonomist. It was quasi-experimental research using one group pre-test and post-test design. The sample was 35 college students chosen by using a purposive sampling technique. The data was gathered using pre-test and post-test techniques of questionnaire distribution. Data analysis was carried out with SPSS by 1) descriptive quantitative analysis on interest; 2) analysis of increasing interest using the N-Gain test; 3) hypothesis analysis using t-test and R2. The results were obtained: 1) the average value of the pre-test on interest was 40,14 (low category) while the post-test was 80,71 (high category); 2) the average value of the N-Gain test on increasing interest was 0,70 (high category); 3) the result of t-test was 0,00 < 0,05 and the result of R2 test was 0,614. Thus, Herbarium-STEM influences students' interest in becoming plant taxonomists, with a high level of influence at 61,4%.